In-service Teachers' Belief and Perspectives on Indonesia's Teacher Professional Education Programme: A Quantitative Study - Tias, Silfia Asning; Sutrisno, Sutrisno; Tongjean, Waraporn (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
This study investigates in-service teachers’ beliefs and perspectives towards teaching, and in specific concerning their participation in the TPE. This research seeks to understand teachers’ beliefs and values in teaching and learning, their needs regarding professional development, their perspectives on the TPE, and how their needs are accommodated in the TPE. This quantitative study involved in-service teachers (n=34) partaking in the TPE and the data collection using a closed-question questionnaire as the research instrument. This study uses descriptive statistics of Relative Important Indices (RII) as data analysis, which is a statistical tool to determine the factors that give weight to the respondents' perceptions by their level of importance. The findings of this study provide insights into teachers’ beliefs toward teaching and their professional practice, which lead to an understanding of their needs for professional education and acknowledging their views of the level of facilitation of their needs in the TPE. The findings highlight teachers’ beliefs in collaboration that are in line with their positive perspective of TPE, which has facilitated collaboration during the programme. The data also shows that 79% of respondents agree that assessment and classroom management should be a priority in the teacher education programme, which is aligned with their views that designing assessment was well facilitated during the subject-specific pedagogy workshop during the TPE. As a high-stakes programme held by the government to improve teachers’ quality in Indonesia, based on the findings it is recommended that TPE be revisited from the teacher’s perspective as the primary stakeholder, such as classroom management training.